GE_GERICHTE P/10993/2024 vom 16. Juni 2025 - GE Cour de justice (2025)
IN DUBIO PRO REO;EXPULSION(DROIT PÉNAL);BRIGANDAGE;VOL(DROIT PÉNAL);DISPOSITIONS PÉNALES DE LA LSTUP | CP.139; LStup.19; CP.140; LStup.19a; CP.66A